High-strength non-stick aluminum castable for tilting type aluminum melting furnace and preparation method of high-strength non-stick aluminum castable
Through the preparation method of raw material composition without SiO2 and the dry mixing and then wet mixing, the problems of poor structural stability of the castable material in the tilt-type aluminum furnace during mechanical vibration are solved, and the improvement of high-strength and non-stick aluminum performance is achieved.
Patent Information
- Application Number
- CN202411925607.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-11
AI Technical Summary
When used in tilt-type aluminum melting furnaces, the existing castables have poor structural stability when facing mechanical vibration, their seismic resistance is average, and the improvement of non-stick aluminum performance is limited.
It is composed of raw materials that do not contain SiO2. The aggregate is corundum, Si3N4 particles, Si3N4 whiskers and Si3N4 fibers. The powder is alumina powder. The uniformity and high strength of the material are ensured by dry-mixing first and then wet-mixing.
The high strength and non-stick aluminum properties of the castable are achieved, the vibration resistance and fire resistance are enhanced, and the corundum tumor problem caused by the reaction of SiO2 with liquid aluminum is avoided.
Smart Images

Figure CN119797941A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of refractory castables, and in particular relates to a high-strength non-stick aluminum castable for a tilting aluminum melting furnace and a preparation method thereof. Background Art
[0002] The main function of aluminum melting furnace is to heat solid aluminum alloy materials into liquid state. It is widely used in metal processing, casting and recycling industries. Compared with ordinary aluminum melting furnaces, tilting aluminum melting furnaces have obvious differences in their own structure and usage methods.
[0003] For example, ordinary aluminum melting furnaces cannot rotate and tilt to load and unload materials, and accordingly, they do not have the unique rotation support structure and rotation drive structure of the tilting aluminum melting furnace. The above-mentioned support structure is generally an arc-shaped trough body and an insertion block, and the above-mentioned drive structure is generally a motor and a hinge block.
[0004] On the other hand, it is precisely because the tilting aluminum melting furnace will reciprocate during use, and it is impossible to completely avoid all kinds of vibrations during the rotation process. Therefore, for the tilting aluminum melting furnace, its dedicated castable also needs to take special consideration of the anti-seismic performance to avoid obvious vibration cracks in the castable lining in a short time.
[0005] In addition, whether it is a tilting aluminum melting furnace or an ordinary aluminum melting furnace, its castable needs to have a non-stick aluminum effect, that is, outstanding aluminum liquid wetting performance to avoid the aluminum liquid forming obvious and large amounts of corundum nodules on the lining in a short time.
[0006] The formation principle of the above-mentioned corundum nodules is as follows: the castables commonly used in aluminum melting furnaces mainly consist of Al2O3 and SiO2 as raw materials, and the aluminum liquid has active chemical properties and can easily react with the above-mentioned SiO2 to generate Si and Al2O3, which are the main components of the above-mentioned corundum nodules. Not only will it destroy the lining structure, but it will also dope Si into the aluminum liquid, which will greatly reduce the quality of the aluminum liquid.
[0007] However, it should be noted that SiO2 is very important in the commonly used castables for aluminum melting furnaces. Its functions include at least: enhancing refractoriness, improving fluidity, and providing expansion compensation.
[0008] For example, the Chinese invention patent application with application publication number CN118495969A and application publication date 2024.08.16 discloses a high-strength anti-aluminum liquid wetting castable product for aluminum melting furnaces. The raw material composition of the product includes: corundum with a particle size of ≤5mm, Al2O3-MgO-CaO composite material with a particle size of ≤0.074mm, alumina powder with a particle size of ≤5μm, silica powder with a particle size of ≤2μm, anti-wetting agent, sintering aid, composite reinforcing agent, composite explosion-proof agent, binder and water reducer.
[0009] The anti-aluminum liquid wetting castable in the invention patent application has the advantages of improving the anti-aluminum liquid wetting property of the castable, improving its sintering performance and physical properties under working conditions.
[0010] However, when the aluminum liquid resistant wetting castable is used in a tilting aluminum melting furnace, the following performance deficiencies still exist, specifically: First, its high strength is mainly reflected in its thermal shock resistance. However, when facing long-term and frequent mechanical vibrations, its structural stability is relatively poor, its seismic resistance is average, and vibration cracks are prone to appear on the lining. Second, in order to improve its anti-wetting performance against aluminum liquid, the use of SiO2 has been greatly reduced, but it still includes 3-5% by mass of silica powder. Therefore, the improvement in the above-mentioned wetting performance is relatively small, which is reflected in its room-temperature flexural strength and room-temperature compressive strength. The former has a value of only 21-23MPa, and the latter has a value of only 130-131MPa, both of which are at a level where the improvement effect is not obvious. Summary of the invention
[0011] The invention provides a high-strength non-stick aluminum casting material for a tilting aluminum melting furnace, and the technical problem to be solved is: how to make the casting material have both outstanding aluminum liquid wetting performance and sufficient mechanical vibration resistance performance.
[0012] In addition, the present invention also provides a preparation method and a use method of the above-mentioned casting material.
[0013] The technical solution adopted by the present invention to solve the above problems is: a high-strength non-stick aluminum castable for a tilting aluminum melting furnace, wherein the raw material composition comprises corundum, Si3N4 particles, Si3N4 whiskers, and Si3N4 fibers as aggregates, and the powder is alumina micropowder.
[0014] In the present invention, SiO2 is not used in the raw material composition, so the above-mentioned outstanding non-stick aluminum performance is possessed.
[0015] Correspondingly, without SiO2, the castable should have the following problems: reduced refractoriness, poor fluidity, reduced expansion compensation, and reduced corrosion resistance. In the present invention, all of the above problems are fully solved through a new raw material composition. The principle is as follows: First, appropriately increase the amount of alumina powder to replace part of SiO2 to ensure that the filling function of the powder base is maintained; Second, Si3N4 material has higher refractoriness than SiO2; Third, the size and shape of Si3N4 particles, Si3N4 whiskers and Si3N4 fibers are differentiated, so that the Si3N4 material part has both the high fluidity of particles and the expansion and deformation compensation function of lines; Fourth, Si3N4 particles, Si3N4 whiskers and Si3N4 fibers are all Si3N4 materials. The three have consistent thermodynamic properties in high temperature environments, so they can make the lining structure of the smelting furnace more compact and stable, and harmful thermochemical reactions are not easy to occur between internal materials. Ultimately, the lining structure is reflected in relatively high corrosion resistance and vibration resistance. Fifth, although the cost of the above-mentioned Si3N4 material is relatively high compared with SiO2, its own strength is greater. The Si3N4 particles, Si3N4 whiskers and Si3N4 fibers have similar performance characteristics of the same material, which makes the internal bonding of the lining structure more dense. When facing the vibration of the tilting aluminum melting furnace, the lining structure itself is not easily vibrated and broken, so it has the above-mentioned advantage of high strength.
[0016] A further preferred technical solution is that the particle size of the corundum is 3.5-5.0 mm, and its weight is 75-85% of the total weight of the aggregate.
[0017] A further preferred technical solution is that: the particle size of the Si3N4 particles is 5.5-8.5 mm, and their weight is 5-10% of the total weight of the aggregate; the average diameter of the Si3N4 whiskers is 8-12 μm, the length is 42-45 μm, and their weight is 0.1-2.0% of the total weight of the aggregate; the average diameter of the Si3N4 fibers is 4-15 μm, the length is 80-115 μm, and their weight is the remainder of the total weight of the aggregate.
[0018] A further preferred technical solution is that the particle size of the alumina powder is 3.0-5.2 μm, and its weight is 11-14% of the total weight of the raw materials.
[0019] A further preferred technical solution is that the raw material composition also includes a binder, an additive and water, the binder includes aluminum phosphate and calcium aluminate cement, and the additive includes calcium lignin sulfonate water reducer and polypropylene explosion-proof fiber.
[0020] A further preferred technical solution is that the raw material composition is the following components by weight: 72% aggregate, 13% powder, 9% binder, 2% additive, and 4% water.
[0021] A method for preparing a high-strength non-stick aluminum castable for a tilting aluminum melting furnace comprises the following steps in sequence: S1, dry mixing: adding the corundum powder, Si3N4 particles, aluminum phosphate, and calcium aluminate cement into a stirrer, and stirring to obtain a dry material; S2. Wet mixing: adding the Si3N4 whiskers, Si3N4 fibers, alumina powder, calcium lignin sulfonate water reducer, polypropylene explosion-proof fibers, and water to the dry material, and stirring to obtain the final castable.
[0022] In the present invention, the above-mentioned method of dry mixing first and then wet mixing has the following advantages compared with the method of adding water to all the raw materials and stirring them together: Avoid relatively long Si3N4 whiskers, Si3N4 fibers and polypropylene explosion-proof fibers, which may cause harmful effects on granular and powdery raw materials, making them difficult to disperse evenly.
[0023] A method for using a high-strength non-stick aluminum castable for a tilting aluminum melting furnace comprises the following steps in sequence: T1. Forming: adding the castable material into the mold of the lining of the tilting aluminum melting furnace by pouring and vibrating through a pouring device to obtain a lining precursor; T2, curing: putting the lining precursor and the mold together into a curing kiln, and demolding after curing for 10-12 hours to obtain a blank; T3, drying: heating the blank in a drying box to obtain a dried body; T4. Firing: The dried body is fired in a high-temperature furnace to obtain the final lining of the tilting aluminum melting furnace.
[0024] A further preferred technical solution is that in T2, the internal humidity of the curing kiln is 80-90% and the temperature is 25-28°C.
[0025] A further preferred technical solution is that in T3, the temperature of the heating operation is 120-130°C and the time is 8.0-12.5h; in T4, the temperature of the firing operation is 850-950°C and the time is 1.0-1.5h.
[0026] The beneficial effects of the present invention include at least the following three points.
[0027] First, the raw material composition of the castable does not use SiO2 at all, so the problem of corundum nodules caused by the reaction of SiO2 with aluminum liquid can be eliminated, corresponding to the above-mentioned non-stick aluminum advantage.
[0028] Second, compared with SiO2, Si3N4 material itself has higher refractoriness, but through the reasonable grading of homogeneous and different forms of particles, whiskers and fibers, the structure of the lining of the aluminum melting furnace is more compact. When facing tilting operation, it is not easy to cause harmful phenomenon of self-rupture due to vibration, which corresponds to the above-mentioned advantage of high strength.
[0029] Third, in the preparation method of the castable, by first dry mixing and then wet mixing, the influence of whisker materials and fiber materials on the uniformity of mixing all materials is fully reduced, and finally it is ensured that the lining of the aluminum melting furnace has sufficient uniformity and consistency in the thickness direction and in the length and width direction. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 These are the test results of high strength and non-stick aluminum performance of the castable samples in four embodiments and five comparative examples of the present invention. DETAILED DESCRIPTION
[0031] The following descriptions are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention.
[0032] Example 1 As attached Figure 1 As shown, a high-strength non-stick aluminum castable for a tilting aluminum melting furnace comprises a raw material composition in which the aggregate is corundum, Si3N4 particles, Si3N4 whiskers, and Si3N4 fibers, and the powder is alumina micropowder.
[0033] The particle size of the corundum is 3.7-4.9 mm, and its weight accounts for 78% of the total weight of the aggregate.
[0034] The particle size of the Si3N4 particles is 5.7-8.2 mm, and their weight is 9% of the total weight of the aggregate; the average diameter of the Si3N4 whiskers is 8-9 μm, the length is 43-45 μm, and their weight is 1.2% of the total weight of the aggregate; the average diameter of the Si3N4 fibers is 5-7 μm, the length is 82-107 μm, and their weight is the remainder of the total weight of the aggregate, i.e., 11.8%.
[0035] The particle size of the alumina powder is 3.8-5.2 μm.
[0036] The raw material composition also includes a binder, an additive and water, wherein the binder is aluminum phosphate and calcium aluminate cement, and the additive is a calcium lignin sulfonate water reducer and polypropylene explosion-proof fiber. Specifically, the raw material composition is the following components by weight: 72% aggregate, 13% powder, 9% binder, 2% additive, and 4% water.
[0037] The method for preparing the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: S1, dry mixing: adding the corundum powder, Si3N4 particles, aluminum phosphate, and calcium aluminate cement into a stirrer, and stirring to obtain a dry material; S2. Wet mixing: adding the Si3N4 whiskers, Si3N4 fibers, alumina powder, calcium lignin sulfonate water reducer, polypropylene explosion-proof fibers, and water to the dry material, and stirring to obtain the final castable.
[0038] The method for using the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: T1. Forming: adding the castable material into the mold of the lining of the tilting aluminum melting furnace by pouring and vibrating through a pouring device to obtain a lining precursor; T2, curing: putting the lining precursor and the mold together into a curing kiln, and demolding after curing for 10 hours to obtain a blank; T3, drying: heating the blank in a drying box to obtain a dried body; T4. Firing: The dried body is fired in a high-temperature furnace to obtain the final lining of the tilting aluminum melting furnace.
[0039] In T2, the internal humidity of the curing kiln was 87% and the temperature was 28°C.
[0040] In T3, the heating operation temperature is 124°C and the time is 9.5 h.
[0041] In T4, the firing operation temperature is 950°C and the time is 1.5 h.
[0042] Example 2 As attached Figure 1 As shown, a high-strength non-stick aluminum castable for a tilting aluminum melting furnace comprises a raw material composition in which the aggregate is corundum, Si3N4 particles, Si3N4 whiskers, and Si3N4 fibers, and the powder is alumina micropowder.
[0043] The particle size of the corundum is 4.1-5.0 mm, and its weight accounts for 82% of the total weight of the aggregate.
[0044] The particle size of the Si3N4 particles is 5.7-8.2 mm, and their weight is 10% of the total weight of the aggregate; the average diameter of the Si3N4 whiskers is 8-11 μm, the length is 43-45 μm, and their weight is 1.0% of the total weight of the aggregate; the average diameter of the Si3N4 fibers is 5-7 μm, the length is 91-101 μm, and their weight is the remainder of the total weight of the aggregate, i.e., 7%.
[0045] The particle size of the alumina powder is 3.1-4.5 μm.
[0046] The raw material composition also includes a binder, an additive and water, wherein the binder is aluminum phosphate and calcium aluminate cement, and the additive is a calcium lignin sulfonate water reducer and polypropylene explosion-proof fiber. Specifically, the raw material composition is the following components by weight: 70% aggregate, 11% powder, 9% binder, 6% additive, and 4% water.
[0047] The method for preparing the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: S1, dry mixing: adding the corundum powder, Si3N4 particles, aluminum phosphate, and calcium aluminate cement into a stirrer, and stirring to obtain a dry material; S2. Wet mixing: adding the Si3N4 whiskers, Si3N4 fibers, alumina powder, calcium lignin sulfonate water reducer, polypropylene explosion-proof fibers, and water to the dry material, and stirring to obtain the final castable.
[0048] The method for using the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: T1. Forming: adding the castable material into the mold of the lining of the tilting aluminum melting furnace by pouring and vibrating through a pouring device to obtain a lining precursor; T2, curing: putting the lining precursor and the mold together into a curing kiln, and demolding after curing for 10 hours to obtain a blank; T3, drying: heating the blank in a drying box to obtain a dried body; T4. Firing: The dried body is fired in a high-temperature furnace to obtain the final lining of the tilting aluminum melting furnace.
[0049] In T2, the internal humidity of the curing kiln was 89% and the temperature was 28°C.
[0050] In T3, the heating operation temperature is 130°C and the time is 9.5 h.
[0051] In T4, the firing operation temperature is 900°C and the time is 1.5 h.
[0052] Example 3 As attached Figure 1 As shown, a high-strength non-stick aluminum castable for a tilting aluminum melting furnace comprises a raw material composition in which the aggregate is corundum, Si3N4 particles, Si3N4 whiskers, and Si3N4 fibers, and the powder is alumina micropowder.
[0053] The particle size of the corundum is 4.1-4.8 mm, and its weight accounts for 81% of the total weight of the aggregate.
[0054] The particle size of the Si3N4 particles is 5.7-8.4 mm, and their weight is 7% of the total weight of the aggregate; the average diameter of the Si3N4 whiskers is 8-11 μm, the length is 43-45 μm, and their weight is 2% of the total weight of the aggregate; the average diameter of the Si3N4 fibers is 5-7 μm, the length is 91-114 μm, and their weight is the remainder of the total weight of the aggregate, i.e., 10%.
[0055] The particle size of the alumina powder is 3.1-4.9 μm.
[0056] The raw material composition also includes a binder, an additive and water, wherein the binder is aluminum phosphate and calcium aluminate cement, and the additive is a calcium lignin sulfonate water reducer and polypropylene explosion-proof fiber. Specifically, the raw material composition is the following components by weight: 70% aggregate, 13% powder, 10% binder, 5% additive, and 2% water.
[0057] The method for preparing the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: S1, dry mixing: adding the corundum powder, Si3N4 particles, aluminum phosphate, and calcium aluminate cement into a stirrer, and stirring to obtain a dry material; S2. Wet mixing: adding the Si3N4 whiskers, Si3N4 fibers, alumina powder, calcium lignin sulfonate water reducer, polypropylene explosion-proof fibers, and water to the dry material, and stirring to obtain the final castable.
[0058] The method for using the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: T1. Forming: adding the castable material into the mold of the lining of the tilting aluminum melting furnace by pouring and vibrating through a pouring device to obtain a lining precursor; T2, curing: putting the lining precursor and the mold together into a curing kiln, and demolding after curing for 12 hours to obtain a blank; T3, drying: heating the blank in a drying box to obtain a dried body; T4. Firing: The dried body is fired in a high-temperature furnace to obtain the final lining of the tilting aluminum melting furnace.
[0059] In T2, the internal humidity of the curing kiln was 89% and the temperature was 28°C.
[0060] In T3, the heating operation temperature is 130°C and the time is 10.0 h.
[0061] In T4, the firing operation temperature is 900°C and the time is 1.0h.
[0062] Example 4 As attached Figure 1 As shown, a high-strength non-stick aluminum castable for a tilting aluminum melting furnace comprises a raw material composition in which the aggregate is corundum, Si3N4 particles, Si3N4 whiskers, and Si3N4 fibers, and the powder is alumina micropowder.
[0063] The particle size of the corundum is 3.6-4.8 mm, and its weight accounts for 79% of the total weight of the aggregate.
[0064] The particle size of the Si3N4 particles is 5.9-8.4 mm, and their weight is 7% of the total weight of the aggregate; the average diameter of the Si3N4 whiskers is 8-11 μm, the length is 43-45 μm, and their weight is 0.5% of the total weight of the aggregate; the average diameter of the Si3N4 fibers is 5-7 μm, the length is 91-97 μm, and their weight is the remainder of the total weight of the aggregate, i.e., 13.5%.
[0065] The particle size of the alumina powder is 3.1-4.7 μm.
[0066] The raw material composition also includes a binder, an additive and water, wherein the binder is aluminum phosphate and calcium aluminate cement, and the additive is a calcium lignin sulfonate water reducer and polypropylene explosion-proof fiber. Specifically, the raw material composition is the following components by weight: 72% aggregate, 12% powder, 8% binder, 5% additive, and 3% water.
[0067] The method for preparing the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: S1, dry mixing: adding the corundum powder, Si3N4 particles, aluminum phosphate, and calcium aluminate cement into a stirrer, and stirring to obtain a dry material; S2. Wet mixing: adding the Si3N4 whiskers, Si3N4 fibers, alumina powder, calcium lignin sulfonate water reducer, polypropylene explosion-proof fibers, and water to the dry material, and stirring to obtain the final castable.
[0068] The method for using the high-strength non-stick aluminum castable for the tilting aluminum melting furnace comprises the following steps in sequence: T1. Forming: adding the castable material into the mold of the lining of the tilting aluminum melting furnace by pouring and vibrating through a pouring device to obtain a lining precursor; T2, curing: putting the lining precursor and the mold together into a curing kiln, and demolding after curing for 12 hours to obtain a blank; T3, drying: heating the blank in a drying box to obtain a dried body; T4. Firing: The dried body is fired in a high-temperature furnace to obtain the final lining of the tilting aluminum melting furnace.
[0069] In T2, the internal humidity of the curing kiln was 85% and the temperature was 28°C.
[0070] In T3, the heating operation temperature is 130°C and the time is 10.0 h.
[0071] In T4, the firing operation temperature is 940°C and the time is 1.0 h.
[0072] Comparative Example 1 The castable in this comparative example has only one difference from Example 1 in terms of raw material composition, preparation method and use method: The Si3N4 particles, Si3N4 whiskers, and Si3N4 fibers are replaced as a whole with SiO2 particles of the same weight, the particle size of which is 3.2-4.7 mm.
[0073] Comparative Example 2 The castable in this comparative example has only one difference from Example 1 in terms of raw material composition, preparation method and use method: The alumina powder is replaced by an equal amount of SiO2 powder, the particle size of which is 4.0-4.8 μm.
[0074] Comparative Example 3 The castable in this comparative example has only one difference from Example 1 in terms of raw material composition, preparation method and use method: The Si3N4 whiskers and Si3N4 fibers are replaced by Si3N4 particles of the same weight, that is, the aggregates are corundum powder and Si3N4 particles.
[0075] Comparative Example 4 The castable in this comparative example has only one difference from Example 1 in terms of raw material composition, preparation method and use method: The Si3N4 particles and Si3N4 whiskers are replaced by Si3N4 fibers of the same weight, that is, the aggregates are corundum powder and Si3N4 fibers.
[0076] Comparative Example 5 The castable in this comparative example has only one difference from Example 1 in terms of raw material composition, preparation method and use method: That is, in the preparation method, all raw materials are added together in a stirrer and stirred to obtain the final casting material.
[0077] Performance test In the four embodiments and five comparative examples, 10 samples were taken respectively, of which 8 samples were used for performance testing and the remaining 2 samples were used for crucible testing. The final average results are shown in the attached Figure 1 .
[0078] Among them, the aluminum alloy material melted in the crucible test is 6061 aluminum alloy, the melting temperature is 900℃, and the melting time is 24h to ensure that the aluminum alloy is fully melted. Then it is cooled to room temperature with the furnace, and the crucible is cut along the central axis to observe the alloy morphology and crucible nodule condition.
[0079] Data analysis The castables in the first and fourth embodiments all have sufficient anti-vibration performance and outstanding non-stick aluminum effect. The former is specifically manifested as: room temperature flexural strength ≥ 24.9MPa, room temperature compressive strength ≥ 130.2MPa, and the latter is specifically manifested as: the number of corundum nodules on the inner wall of the crucible is extremely small and almost invisible.
[0080] Second, the casting materials in Comparative Examples 1 and 2 both use SiO2 components, resulting in a relatively large number of corundum nodules, which is consistent with the forming principle of corundum nodules. The above-mentioned outstanding non-stick aluminum effect must be achieved without using any form of SiO2 components.
[0081] Third, the casting materials in Comparative Examples 3 and 4 did not make reasonable grade adaptation for Si3N4 materials, resulting in reduced anti-vibration performance.
[0082] Fourth, the "one-step" preparation method of the castable in Comparative Example 5 makes it difficult to fully mix the materials, especially when Si3N4 whiskers, Si3N4 fibers and polypropylene explosion-proof fibers are used. The degree of uneven mixing is more obvious, which is ultimately reflected in the castable as a reduction in mechanical properties and in the lining of the aluminum melting furnace as a reduction in anti-vibration performance.
[0083] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various modifications can be made within the knowledge of ordinary technicians in the technical field without departing from the purpose of the present invention. These are all non-creative modifications and are protected by patent law as long as they are within the scope of the claims of the present invention.
Claims
1. A high-strength non-stick aluminum castable for a tilting aluminum melting furnace, characterized in that: In the raw material composition, the aggregate is corundum, Si3N4 particles, Si3N4 whiskers, and Si3N4 fibers, and the powder is alumina powder.
2. The high-strength non-stick aluminum castable for a tilting aluminum melting furnace according to claim 1, characterized in that: The particle size of the corundum is 3.5-5.0 mm, and its weight accounts for 75-85% of the total weight of the aggregate.
3. The high-strength non-stick aluminum castable for a tilting aluminum melting furnace according to claim 2, characterized in that: The particle size of the Si3N4 particles is 5.5-8.5 mm, and their weight is 5-10% of the total weight of the aggregate; the average diameter of the Si3N4 whiskers is 8-12 μm, the length is 42-45 μm, and their weight is 0.1-2.0% of the total weight of the aggregate; the average diameter of the Si3N4 fibers is 4-15 μm, the length is 80-115 μm, and their weight is the remainder of the total weight of the aggregate.
4. The high-strength non-stick aluminum castable for a tilting aluminum melting furnace according to claim 1, characterized in that: The particle size of the alumina powder is 3.0-5.2 μm, and its weight is 11-14% of the total weight of the raw materials.
5. The high-strength non-stick aluminum castable for a tilting aluminum melting furnace according to claim 1, characterized in that: The raw material composition also includes a binder, an additive and water. The binder includes aluminum phosphate and calcium aluminate cement, and the additive includes calcium lignin sulfonate water reducer and polypropylene explosion-proof fiber.
6. The high-strength non-stick aluminum castable for a tilting aluminum melting furnace according to claim 1, characterized in that The raw material composition is the following components by weight: aggregate 72%, powder 13%, binder 9%, additive 2%, and water 4%.
7. A method for preparing a high-strength non-stick aluminum castable for a tilting aluminum melting furnace as claimed in claim 5, characterized in that The following steps are included in sequence: S1, dry mixing: adding the corundum powder, Si3N4 particles, aluminum phosphate, and calcium aluminate cement into a stirrer, and stirring to obtain a dry material; S2. Wet mixing: adding the Si3N4 whiskers, Si3N4 fibers, alumina powder, calcium lignin sulfonate water reducer, polypropylene explosion-proof fibers, and water to the dry material, and stirring to obtain the final castable.
8. A method for using the high-strength non-stick aluminum castable for a tilting aluminum melting furnace as claimed in claim 5, characterized in that The following steps are included in sequence: T1. Forming: adding the castable material into the mold of the lining of the tilting aluminum melting furnace by pouring and vibrating through a pouring device to obtain a lining precursor; T2, curing: putting the lining precursor and the mold together into a curing kiln, and demolding after curing for 10-12 hours to obtain a blank; T3, drying: heating the blank in a drying box to obtain a dried body; T4. Firing: The dried body is fired in a high-temperature furnace to obtain the final lining of the tilting aluminum melting furnace.
9. The method for using the high-strength non-stick aluminum castable for a tilting aluminum melting furnace according to claim 8, characterized in that: In T2, the internal humidity of the curing kiln was 80-90% and the temperature was 25-28°C.
10. The method for using the high-strength non-stick aluminum castable for a tilting aluminum melting furnace according to claim 8, characterized in that: In T3, the temperature of the heating operation is 120-130°C and the time is 8.0-12.5h; in T4, the temperature of the firing operation is 850-950°C and the time is 1.0-1.5h.
Citation Information
Patent Citations
High-strength molten aluminum wetting resistant castable product for aluminum melting furnace and process
CN118495969A